Nivel de apalancamiento y estabilidad financiera empresarial: el caso de firmas de Colombia y Argentina (2018)
This paper aims to explain the effect of financial instability on the capital structure of firms in two emerging markets: Colombia and Argentina. For the analysis, the study uses an unbalanced panel dataset with 167 companies, with quarterly data between 2005 and 2015, and regressions with the random-effects method. The results show that lower liquidity level and losses during two or more consecutive quarters increase the level of leverage in companies; therefore, signs of financial insolvency lead firms to become over-indebted and to reproduce the same conditions that lead to the emergence of a financial crisis